Islamic Psychology as A Contextual and Actual Tafsir Approach - Zakiyah, Ermita (Proceedings Conference Psychology and Flourishing Humanity; Vol 1 No 1 (2024): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
The understanding of modern psychology that is far from Islamic teachings is an incomplete problem, even though Islamic psychology has developed long before modern psychology emerged and the cumulative efforts of Islamic Psychology are increasingly interesting and fertile to be discussed, a rich discourse that needs to be nurtured and become a challenge as well as an opportunity for Muslims and the world of Psychology today. The Qur'an as a guide for Muslims with the jargon solih li kulli Zaman wa makan becomes the starting point that the Qur'an always goes hand in hand with technology and increasingly diverse human understanding, so that contextual and actual interpretations are needed. The data collection technique of this article is in the form of library research with the method of describing each problem and then analyzing it so that a thorough understanding is obtained, so that the theory of Islamic integrated psychology becomes a complete concept and can be used in the world of modern psychology.